Quorum Sensing-Mediated and Growth Phase-Dependent Regulation of Metabolic Pathways in Hafnia alvei H4 - Yan, Congyang; Li, Xue; Zhang, Gongliang; Zhu, Yaolei; Bi, Jingran; Hao, Hongshun; Hou, Hongman (Frontiers in Microbiology, 2021)
Quorum sensing (QS) is a widespread regulatory mechanism in bacteria used to coordinate target gene expression with cell density. Thus far, little is known about the regulatory relationship between QS and cell density in terms of metabolic pathways in Hafnia alvei H4. In this study, transcriptomics analysis was performed under two conditions to address this question. The comparative transcriptome of H. alvei H4 wild-type at high cell density (OD600 = 1.7) relative to low cell density (OD600 = 0.3) was considered as growth phase-dependent manner (GPDM), and the transcriptome profile of luxI/R deletion mutant (ΔluxIR) compared to the wild-type was considered as QS-mediated regulation. In all, we identified 206 differentially expressed genes (DEGs) mainly presented in chemotaxis, TCA cycle, two-component system, ABC transporters and pyruvate metabolism, co-regulated by the both density-dependent regulation, and the results were validated by qPCR and swimming phenotypic assays. Aside from the co-regulated DEGs, we also found that 59 DEGs, mediated by density-independent QS, function in pentose phosphate and histidine metabolism and that 2084 cell-density-dependent DEGs involved in glycolysis/gluconeogenesis and phenylalanine metabolism were influenced only by GPDM from significantly enriched analysis of transcriptome data. The findings provided new information about the interplay between two density-dependent metabolic regulation, which could assist with the formulation of control strategies for this opportunistic pathogen, especially at high cell density.